2017
DOI: 10.5114/wiitm.2016.65078
|View full text |Cite
|
Sign up to set email alerts
|

Stress as a factor contributing to obesity in patients qualified for bariatric surgery - studies in a selected group of patients (a pilot study).

Abstract: IntroductionRecently, the incidence of obesity, especially extreme obesity, has significantly increased. It is connected with inappropriate lifestyle, including a high calorie diet, psychological and genetic factors, some medications, diseases or infectious factors. Nowadays, the consumption of food is not only to satisfy a physiological need, but also fulfils psychological needs. The most effective method of morbid obesity treatment is metabolic surgery. Moreover, food is considered to be a reward and method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…The LSG is one of the most effective methods for obesity treatment and stands out to fulfill requirements demanded for appropriate therapy in the whole MS area, in cooperation with diet, psychological treatment, lifestyle modifications and all other supportive therapy methods. Such a conclusion is widely confirmed also in current scientific literature [24][25][26], whereas standalone therapeutic efficiency of mentioned conservative methods usage without bariatric treatment remains unsatisfactory and rarely provides desired positive long-term outcome [27]. When focusing on particular MS components, results achieved in our observation lead to the conclusion that undergoing the LSG operation not only effectively treats existing NIDDM cases, but also enforces normalization of glucose metabolism parameters and prevents development of NIDDM by treating the insulin resistance phenomenon.…”
Section: Niddm Arterial Hypertension Partial Remission (%)supporting
confidence: 76%
“…The LSG is one of the most effective methods for obesity treatment and stands out to fulfill requirements demanded for appropriate therapy in the whole MS area, in cooperation with diet, psychological treatment, lifestyle modifications and all other supportive therapy methods. Such a conclusion is widely confirmed also in current scientific literature [24][25][26], whereas standalone therapeutic efficiency of mentioned conservative methods usage without bariatric treatment remains unsatisfactory and rarely provides desired positive long-term outcome [27]. When focusing on particular MS components, results achieved in our observation lead to the conclusion that undergoing the LSG operation not only effectively treats existing NIDDM cases, but also enforces normalization of glucose metabolism parameters and prevents development of NIDDM by treating the insulin resistance phenomenon.…”
Section: Niddm Arterial Hypertension Partial Remission (%)supporting
confidence: 76%
“…Moreover, the patients admitted that they needed psychological support and support for diet and physical activity. It has also been emphasized in the literature that support groups play an important role in weight loss (Hall, 2010; Ruffault et al, 2018) and facilitate adaptation to changes in life-style (Boniecka, Wileńska, Jeznach-Steinhagen, Czerwonogrodzka-Senczyna, Sekuła, & Paśnik, 2017; Følling, Solbjør, & Helvik, 2015; Tarrant et al, 2017). Therefore, it is crucial that nurses should adopt a holistic approach taking account of both physiological and biopsychological needs and determine knowledge needs of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are emotional eaters should receive special care [ 5 ]. In Boniecka’s research stress was found to be one of the most frequent causes of eating between meals, and moreover a large part of the patients reported an increase in appetite due to stressful situations [ 20 ]. Regular medical checkups before and after surgery as well as family support are essential because dramatic weight loss is a life-changing experience.…”
Section: Preoperative Assessmentmentioning
confidence: 99%